Review of Redox Flow Batteries as Back Up Storage For Retaining Block Wall For I-Flow Project - Mohd Rusllim, Mohamed; M. S., Najib (2013)

(untitled)
A significant research in redox flow battery (RFB) has been carried out by numerous researchers; some are under field testing and demonstration stage, yet several technological challenges remain in the optimisation and improvement of current RFB.